Investigations of Flare Gas Emissions in Taq Taq Oil Field on the Surrounding Land - Ali, Jafar A.; Khodakarami, Loghman A. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2014)
Environmental pollution caused by oil takes many different forms; one of the most damaging sources is simply the combustion of oil products, such as a well flare burn-off. This paper presents the results of a survey of the agriculture lands around the Taq Taq Oil Production Company. The aim of the survey was to determine the potential contamination caused by the gas emissions from the well flares. Taq Taq field is located in the Kurdistan Region of Iraq, 60 km north of the giant Kirkuk oil field, 85 km south-east of Erbil and 120 km north-west of Suleimani. Samples of soil were collected from several locations around the site and analyzed to determine the content of Polycyclic Aromatic Hydrocarbons PAH present. A gas chromatography linked to a mass spectrometry (GCMS) machine was used for these measurements. The PAH contamination at each location of soil was determined and the 16-PAHs, as listed in the US Environmental Protection Agency (EPA) documentation were investigated. The average content of total PAH in all samples of the agricultural soil was 0.654 mg·kg-1 with the concentrations ranging from 0.310 to 0.869 mg·kg-1. It was found that the PAH concentrations decreased with increasing distance from the TTOPCO oil field, indicating that pollution was evident, the area close to the field being more affected by the gas pollution.